International working group on determination of age and growth rate in tropical trees: address list and subject categories - Burley, J (Commenwealth Forestry Institute, University of Oxford, 1985)
In 1980 a workshop sponsored by the US National Academy of Sciences was held at Harvard Forest, Petersham, Massachusetts, USA, on 'Determination of age and growth rate in tropical trees: new directions for research'. This gave rise, inter alia, to Bulletin No 94 of the Yale University School of Forestry and Environmental Studies 'Age and growth rate of tropical trees', edited by F.H. Bormann and G. Berlyn; the table of contents of this Bulletin is shown as Annex 1 to this report. In view of the rapid destruction of tropical forest and the urgent need to evaluate ecological and managerial systems for its maintenance, it is essential to develop techniques for age determination in tropical trees. The Bulletin reviewed the published information and included the expertise of the 27 scientists from 12 countries participating in the workshop. It was clear, however, that other researchers elsewhere had active interests and a small committee was established to locate these and classify them by the techniques they were using. Questionnaires were circulated in English, French, Portuguese and Spanish to some 1000 addresses. The questionnaires are included in Annex 2 and the members of the committee in Annex 3. The present report lists 77 workers who responded up to the end of 1984. In the period since the workshop new techniques may have emerged and additional scientists may have begun research on tropical trees. However, this. list provides a starting point and it is proposed to hand it over to the coordinator of Division 5 of the International Union of Forestry Research Organisations (Dr R.L. Youngs, Forest Products Laboratory, Madison, Wisconsin, USA) with a view to determining the interest in forming a Working Party within Subject Group 55.01 (Wood quality).